Effect of Root Canal Sealers on Bond Strength of Fiber Posts to Root Dentin Cemented after one Week or six Months - Ruiz, Lucas; Gomes, Giovana Mongruel; Bittencourt, Bruna; da Silva, Fabricio Rutz; Gomes, Osnara Maria Mongruel; Chidoski Filho, Julio Cezar; Calixto, Abraham Lincoln (Iranian Endodontic Journal, 2019)
Eugenol-based root canal sealers (RCS) have been widely used by clinicians; however, their effect on resinous materials is still questionable. The objective of this study was to evaluate the influence of RCS at 1 week and 6 months’ post obturation on the bond strength (BS) of glass fiber posts (GFP) to root dentin, using conventional and self-adhesive cementation systems (CS). The roots of 56 extracted human canines, were divided in eight groups (n=7) according to the combination of the following factors: RCS (with or without eugenol-Endofill and Sealer 26, respectively), storage period post obturation and prior GFP cementation (1 week and 6 months) and cementation systems (Variolink II - conventional resin cement or RelyX U200-self-adhesive resin cement). After one week, the specimens were transversely sectioned into six 1-mm-thick disks and were subjected to the push out BS test. The data were subjected to 3-way ANOVA and Tukey’s tests (α=0.05). The BS were not affected by the RCS, neither the CS (P>0.05). Just the period post obturation showed statistically significant differences (P£0.05), where the GFP cemented 6 months after the endodontic treatment showed higher values than those cemented 1 week after it. Keywords: Cementation; Dentin; Push-out Bond Strength; Resin Cements; Zinc Oxide Eugenol Cement